2017
DOI: 10.18632/oncotarget.19411
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the BIM BH3 domain overcomes resistance to EGFR tyrosine kinase inhibitors in EGFR-mutant non-small cell lung cancer

Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) are widely applied to treat EGFR-mutant non-small cell lung cancer (NSCLC). BIM is a BH3 domain-containing protein encoded by BCL2L11. Some EGFR-mutant NSCLC patients showing BIM deletion polymorphism are resistant to EGFR TKIs. We retrospectively investigated BIM deletion polymorphism in NSCLC patients, its correlation with EGFR TKI (erlotinib) resistance, and the mechanism underlying the drug resistance. Among 245 EGFR-mutant NSCLC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…On the other hand, the decreased expression of EGFR and increased expression of p-Akt were observed in H1975AR compare to H1975, which was consistent with the resistant mechanisms of another previously established AZD9291-resistant H1975 (Tang et al 2016). Lung cancer with decreased EGFR expression was reported to be sensitive to the BIM BH3 mimetic drug, navitoclax (ABT-263) (Niederst et al 2015;Xia et al 2017), and the upregulated BIM, as a proapoptotic member of Bcl-2 family, was required for apoptosis induced by EGFR-TKIs (Huang and Fu 2015;Xia et al 2017). ABT-263 was also reported to be effective in overcoming the acquired resistance of AZD9291 in AZD9291-resistant H1975 by inhibition of Bcl2 and activation of caspase (Tang et al 2016).…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, the decreased expression of EGFR and increased expression of p-Akt were observed in H1975AR compare to H1975, which was consistent with the resistant mechanisms of another previously established AZD9291-resistant H1975 (Tang et al 2016). Lung cancer with decreased EGFR expression was reported to be sensitive to the BIM BH3 mimetic drug, navitoclax (ABT-263) (Niederst et al 2015;Xia et al 2017), and the upregulated BIM, as a proapoptotic member of Bcl-2 family, was required for apoptosis induced by EGFR-TKIs (Huang and Fu 2015;Xia et al 2017). ABT-263 was also reported to be effective in overcoming the acquired resistance of AZD9291 in AZD9291-resistant H1975 by inhibition of Bcl2 and activation of caspase (Tang et al 2016).…”
Section: Discussionsupporting
confidence: 72%
“…Consequently, this polymorphism impairs the generation of the proapoptotic isoform of BIM required for EGFR-TKI-induced apoptosis and confers an intrinsically TKI-resistant phenotype that can partly explain the heterogeneity of TKI responses across individuals [220]. Indeed, Asian patients with EGFR M+ NSCLC, who harbored this host BIM deletion polymorphism, exhibited significantly inferior responses to treatment with TKIs of all three generations and much shorter PFS than individuals lacking the polymorphism, suggesting that the BIM polymorphism is a negative predictive marker of response to EGFR-TKIs [218,219,220,221,222]. Of note, preclinical experiments indicate that BH3-mimetics or HDAC-inhibitors, such as vorinostat, can restore BIM functionality and sensitivity to EGFR-TKIs in EGFR M+ NSCLC cells carrying the BIM polymorphism [221,222,223].…”
Section: Clinical and Preclinical Studies Shedding Light On Intrinmentioning
confidence: 99%
“…Indeed, Asian patients with EGFR M+ NSCLC, who harbored this host BIM deletion polymorphism, exhibited significantly inferior responses to treatment with TKIs of all three generations and much shorter PFS than individuals lacking the polymorphism, suggesting that the BIM polymorphism is a negative predictive marker of response to EGFR-TKIs [218,219,220,221,222]. Of note, preclinical experiments indicate that BH3-mimetics or HDAC-inhibitors, such as vorinostat, can restore BIM functionality and sensitivity to EGFR-TKIs in EGFR M+ NSCLC cells carrying the BIM polymorphism [221,222,223]. In addition to polymorphism, low BIM expression levels in EGFR M+ NSCLC samples may also predict poorer initial response and shorter duration of clinical benefit from EGFR-TKIs [57,212,224,225].…”
Section: Clinical and Preclinical Studies Shedding Light On Intrinmentioning
confidence: 99%
“…For two studies, each reported two unrelated cohorts [21,23]. Finally, 20 datasets from 18 studies [18][19][20][21][22][23][35][36][37][38][39][40][41][42][43][44][45][46] exploring the association between BIM deletion polymorphism and EGFR-TKI efficacy in EGFR-mutant NSCLC patients were included in our meta-analysis (Figure 1).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%